2020
DOI: 10.3390/mi11100900
|View full text |Cite
|
Sign up to set email alerts
|

Actuating Voltage Waveform Optimization of Piezoelectric Inkjet Printhead for Suppression of Residual Vibrations

Abstract: After a piezoelectric inkjet printhead jets the first droplet, the actuating membrane still vibrates, creating residual vibrations in the ink channel, which can degrade the inkjet printhead performance. For suppressing these vibrations, an optimized actuating voltage waveform with two pulses must be obtained, of which the first pulse is used for jetting and the second pulse is used to suppress the residual vibrations. In this study, the pressure history within the ink channel of a recirculating piezoelectric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…However, the formation of satellites is typically an unwanted feature of inkjet printing technology [ 36 , 37 ]. Liu et al reported that the threshold for satellite formation is a function of Z and the practical range for ink printability is approximately bound by 2 < Z < 20 [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the formation of satellites is typically an unwanted feature of inkjet printing technology [ 36 , 37 ]. Liu et al reported that the threshold for satellite formation is a function of Z and the practical range for ink printability is approximately bound by 2 < Z < 20 [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ink chamber still undergoes pressure oscillations even after the first ink droplet has been ejected under an applied standard voltage waveform using the pull-push actuation mechanism [24]. These undesired pressure oscillations decay after several microseconds, cause variations in the properties of the subsequent ink drops, and form satellites, which degrades the inkjet printhead performance.…”
Section: ) Actuation Mechanisms and Effect Of Voltage Waveformmentioning
confidence: 99%
“…The design of a multipulse waveform has recently been presented as a means of reducing the length of ligament or satellite drops 24 . Hur’s team utilized the lumped element model of a recirculating piezoelectric inkjet printhead to improve bipolar waveforms, demonstrating that a bipolar waveform with a second pulse voltage of 1/3 than that of the first could suppress residual vibrations within the printhead channel 25 . Despite the development in waveform design methodologies, the knowledge of wave propagation and drop formation is limited, and waveform optimization still requires time-consuming and repetitive waveform parameter modifications, while monitoring obtained jetting images.…”
Section: Introductionmentioning
confidence: 99%